The Association Between Protein, Iron, Folate, and Vitamin C Intakes with Hemoglobin Level among Chronic Kidney Disease Patients Undergoing Hemodialysis at Haji Regional Public Hospotal, East Java Province - Ita Nofita Sari; Wildan Alfira Gusrianto; Satwika Arya Pratama; Fista Utami (Journal of Global Nutrition, 2026)
Anemia is a common complication in patients with chronic kidney disease (CKD) undergoing hemodialysis. Anemia in CKD is multifactorial, including impaired erythropoiesis, iron deficiency, and chronic eammation. Adequate nutrient intake plays an essential role in hemoglobin synthesis, anemia management, and improving patient’s quality of life. This study aimed to determine the association between protein, iron, folate, and vitamin C intakes with hemoglobin levels in CKD patients undergoing hemodialysis at Haji Regional Public Hospital, East Java Province. This study used quantitative with cross-sectional design. Purposive sampling was applied, involving 54 respondents who met the inclusion criteria. Data on protein, iron, folate, and vitamin C intakes were collected through direct interviews using semi-quantitative food frequency questionnaire on previous month, while hemoglobin data were obtained from the most recent labolatory recods. Bivariate analysis used the Pearson Corelation test for protein intake and Hb level, while the Spearman test for iron, folate, and vitamin C intakes and Hb level. The results showed that protein intake was significantly associated with hemoglobin level (p=<0.001), with a moderate positive correlation (r=0.45). In contrast, iron, folate, and vitamin C intake were not significantly associated with hemoglobin level (p>0.05). Adequate protein intake, [articularly high biological value anemial protein, is required to compenste for protein losses following dialysis. Personalized protein management based on urea burden, metabolic acidosis, phosphorus status, and comorbidities may support improvements in hemoglobin level without exacerbating renal metabolic burden.